Global patterns in symbiont selection and transmission strategies in sponges - Díez-Vives, Cristina; Koutsouveli, Vasiliki; Conejero, Maria; Riesgo, Ana (Frontiers in Ecology and Evolution, 2022)
Sponges host dense and diverse communities of microbes (known as the microbiome) beneficial for the host nutrition and defence. Symbionts in turn receive shelter and metabolites from the sponge host, making their relationship beneficial for both partners. Given that sponge-microbes associations are fundamental for the survival of both, especially the sponge, such relationship is maintained through their life and even passed on to the future generations. In many organisms, the microbiome has profound effects on the development of the host, but the influence of the microbiome on the reproductive and developmental pathways of the sponges are less understood. In sponges, microbes are passed on to oocytes, sperm, embryos, and larvae (known as vertical transmission), using a variety of methods that include direct uptake from the mesohyl through phagocytosis by oocytes to indirect transmission to the oocyte by nurse cells. Such microbes can remain in the reproductive elements untouched, for transfer to offspring, or can be digested to make the yolky nutrient reserves of oocytes and larvae. When and how those decisions are made are fundamentally unanswered questions in sponge reproduction. Here we review the diversity of vertical transmission modes existent in the entire phylum Porifera through detailed imaging using electron microscopy, available metabarcoding data from reproductive elements, and macroevolutionary patterns associated to phylogenetic constraints. Additionally, we review the fidelity of this vertical transmission and possible reasons for the observed variability in some developmental stages. Our current understanding in marine sponges, however, is that the adult microbial community is established by a combination of both vertical and horizontal (acquisition from the surrounding environment in each new generation) transmission processes, although the extent in which each mode shapes the adult microbiome still remains to be determined. Here we also assessed the fundamental role of filtration, the cellular structures for acquiring external microbes, and the role of the host immune system, that ultimately shapes the stable communities of prokaryotes observed in adult sponges.